2019
DOI: 10.1248/bpb.b19-00127
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Amino Acid Profiles of Blood and Cerebrospinal Fluid from Cystathionine β-Synthase-Deficient Mice, an Animal Model of Homocystinuria

Abstract: Mental retardation is the most common feature among inborn errors of amino acid metabolism. Patients with homocystinuria/homocysteinemia caused by cystathionine β-synthase (CBS) deficiency suffer from thromboembolism and mental retardation from early ages; therefore, detection by newborn screening is performed. Furthermore, elevated levels of serum homocysteine during pregnancy are associated with the occurrence of neural tube defects (NTDs) in newborns. However, the causes of such central nervous system (CNS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Instead, elevated levels of homocyst(e)ine could somehow interfere with oxytocin signaling within the cells (e.g., mammary gland myoepithelial cells). Interestingly, we recently found that the total homocysteine levels of the cerebrospinal fluid were much lower than those of the serum in 2-week-old lactating Cth −/− mice (7.43 versus 184 µM) although both levels were much higher than those in their respective WT mice (1.08 and 13.0 µM, respectively) [57]. This could be the reason for the “semi-” normal oxytocin signaling in the CNS (that regulates maternal behavior in dams and social memory/recognition in males) and the substantially impaired oxytocin signaling in the periphery (that regulates milk ejection/uterine contraction, especially the former in this study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, elevated levels of homocyst(e)ine could somehow interfere with oxytocin signaling within the cells (e.g., mammary gland myoepithelial cells). Interestingly, we recently found that the total homocysteine levels of the cerebrospinal fluid were much lower than those of the serum in 2-week-old lactating Cth −/− mice (7.43 versus 184 µM) although both levels were much higher than those in their respective WT mice (1.08 and 13.0 µM, respectively) [57]. This could be the reason for the “semi-” normal oxytocin signaling in the CNS (that regulates maternal behavior in dams and social memory/recognition in males) and the substantially impaired oxytocin signaling in the periphery (that regulates milk ejection/uterine contraction, especially the former in this study).…”
Section: Discussionmentioning
confidence: 99%
“…This could be the reason for the “semi-” normal oxytocin signaling in the CNS (that regulates maternal behavior in dams and social memory/recognition in males) and the substantially impaired oxytocin signaling in the periphery (that regulates milk ejection/uterine contraction, especially the former in this study). Namely, high circulatory tHcy levels in Cth −/− dams influenced on (high) tHcy in their whey (Table 1) but not circulatory tHcy in their pups (Table 2), and may not affect tHcy in their CNS significantly [57]. Whether hypertension/mild proteinuria in Cth −/− pregnant mice could impair the peripheral oxytocin signaling or vice versa remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although mutations in the Cth gene might even be more prevalent than in the Cbs gene in humans [100], CTH-based models are scarcely utilized in animal research so far, although Cth−/− proved to highly elevate serum and CSF HCys levels [101]. Another example is the betaine homocysteine methyl transferase (BHMT), of which homozygous (Bhmt−/−) and heterozygous (Bhmt+/−) forms were used in order to induce mild HHCys [102].…”
Section: Genetic Inductionmentioning
confidence: 99%
“…Особенностью этих моделей является то, что они не только оказывают непосредственное влияние на транссульфурирование, но сильно влияют на метаболизм физиологического вазодилататора H 2 S. Нокаут гена CBS у мышей линии C57B1/6 был одной из первых моделей гомоцистинурии. Она сопровождалась у гомозигот тяжелой ГГц (>200 мкМ) [22]. В спинномозговой жидкости также наблюдался 25-кратный рост уровня Гцис.…”
Section: Reviewsunclassified
“…Нокаут гена CSE у мышей C57BL/6 также приводил к тяжелой ГГц (~180 мкМ в плазме крови) и 7-кратному возрастанию его уровня в спинномозговой жидкости [22], при этом существенных изменений уровня Цис и Глн в этих жидкостях при этом не наблюдалось.…”
Section: Reviewsunclassified